A cyclic boundary condition for time delayed technical problems and its application for IC-engine simulation. (1st September 2011) - Jajcevic, Dalibor; Almbauer, Raimund A.; Lang, Wolfgang; Schmidt, Stephan
The continuous improvement of numerical methods together with the increase of computer power allows the simulation of more and more complex technical problems even for large calculation domains. Growing calculation domains combined with the simulation of physically complex phenomena increase the simulation effort non-linearly and make them impracticable in the daily work of an engineer. A decrease of simulation time can be realised by the reduction of the calculation domain. In this paper, a new cyclic and time delayed boundary condition is introduced together with its application in the simulation of an IC-engine. The boundary conditions are calculated during the simulation and are set on the corresponding faces in the calculated domain. Furthermore, the data for the boundary condition is deducted from the simulation itself and therefore do not need to come from another software or measurements, what additionally reduces the pre-processing effort.